2009
DOI: 10.1021/jp904003z
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Landscape for the Interaction of the Family 1 Carbohydrate-Binding Module and the Cellulose Surface is Altered by Hydrolyzed Glycosidic Bonds

Abstract: A multiscale simulation model is used to construct potential and free energy surfaces for the carbohydrate-binding module [CBM] from an industrially important cellulase, Trichoderma reesei cellobiohydrolase I, on the hydrophobic face of a coarse-grained cellulose Ibeta polymorph. We predict from computation that the CBM alone exhibits regions of stability on the hydrophobic face of cellulose every 5 and 10 A, corresponding to a glucose unit and a cellobiose unit, respectively. In addition, we predict a new rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 45 publications
6
87
0
Order By: Relevance
“…7B suggests that the enzyme is enthalpically stable above glycosidic linkages separated by ϳ10 Å, where the enzyme can abstract accessible hydrogen atoms. The stabilization every 10 Å, which is approximately the length of a cellobiose unit, is similar to that observed for a family 1 CBM (19,54).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…7B suggests that the enzyme is enthalpically stable above glycosidic linkages separated by ϳ10 Å, where the enzyme can abstract accessible hydrogen atoms. The stabilization every 10 Å, which is approximately the length of a cellobiose unit, is similar to that observed for a family 1 CBM (19,54).…”
Section: Resultssupporting
confidence: 78%
“…Last, a potential energy surface (PES) for the PchGH61D-cellulose interaction was also constructed to examine the location of stable energetic wells. This closely follows previous work conducted on the family 1 CBM (19,54). Details of the PES construction can be found in the supplemental material.…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…Alternatively, the absence of the CBM-linker may significantly decrease the processivity. Regarding this second possibility, Bu et al (38) predicted that the CBM has important roles in not only binding but also introducing a single cellulose chain to the catalytic site and increasing the processivity of the reaction. Their molecular simulation showed that the CBM exerts a driving force and assists processive movement by biased sliding when the CBM binds near the cellulose chain end.…”
mentioning
confidence: 99%
“…Recently, the CBD cellulose complex has been modeled in order to investigate the binding mechanism by molecular dynamics (MD) simulations. It has been suggested that CBD may assist with the recognition of the cellulose chain end and facilitate the processivity of Cel7A [11][12][13]. Beckham et al predicted that electrostatic interactions dominate the energy changes in the Cel7A CBD processivity [12].…”
Section: Introductionmentioning
confidence: 99%